Economic Injury Levels for Aphis glycines Matsumura (Hemiptera: Aphididae) on the Soybean Aphid Tolerant KS4202 Soybean - Marchi-Werle, Lia (2017)
The soybean aphid, Aphis glycines Matsumura (Hemiptera: Aphididae), is an invasive species from Asia that has been the major economic insect pest of soybeans, Glycine max (L.) Merrill, since 2000. While use of soybeans expressing antibiosis and antixenosis is a well-studied strategy to manage this pest, aphid-tolerant soybeans remain underexplored. This study examined the relationship between cumulative aphid-days (CAD) and yield loss in the tolerant soybean KS4202 during two growing seasons to determine the economic injury levels (EILs) for soybean aphids on KS4202. Soybean aphid infestations were initiated during the soybean reproductive stages. A range of CAD treatments (3,000-45,000 CADs) were applied during the growing seasons. Aphid populations reached 45,000 CAD in 2011 and 38,000 CAD in 2013 in plots that were not treated with insecticides. It was estimated that the population doubling time was 9.4 d. In infested plots, soybean yield was reduced by 1.4-13.3%, equivalent to a 3.1% yield loss for every 10,000 CAD. Overall, most CAD treatments did not affect yield parameters, although CAD > 39,000 caused a significant reduction in most yield parameters. The EILs calculated for KS4202 ranged from 526 to 2,050 aphids/plant, which were approximately 2.5-fold higher when compared to EILs previously calculated for susceptible soybean. The adoption of soybean aphid tolerant soybean with higher EILs may help mitigate treatment delay problems by lengthening the treatment lead-time and possibly reduce the number of insecticide applications.